A facile method to prepare high-performance thermal insulation and flame retardant materials from amine-linked porous organic polymers. (5th January 2022) - Zhao, Pengju; Tian, Li; Guo, Yongliang; Lv, Bo; Mao, Xin; Li, Ting; Cui, Jinfeng; Guo, Junhong; Yang, Baoping
Graphical abstract: Highlights: Synthesized phosphorus-containing organic porous polymers (PPOPs) for thermal insulation and flame retardancy. PPOPs have low thermal conductivity and excellent flame retardant properties. Loading PPOPs improved the flame retardant and mechanical properties of EP. PPOPs can be designed into different shapes for practical applications. Abstract: Developing porous functional materials with good thermal insulation and flame retardant properties is of great importance in modern eco-friendly buildings. Herein, we report the one-step synthesis of imine chain monolithic porous phosphorus-containing organic porous polymers (PPOPs) using Schiff base polycondensation reaction and as an example of efficient thermal insulation and flame retardant. Experimental results show that the PPOPs have low thermal conductivity (0.055 W·m −1 ·K −1 ) and excellent flame retardant properties. Measurements by microcalorimetry (MCC) showed a peak heat release rate (pHRR) value was 23.9 W·g −1, which is nearly an order of magnitude lower than that of most currently reported flame retardant materials. Using PPOPs in the epoxy resin (EP) matrix, the prepared EP composites exhibited excellent flame retardant properties. Cone calorimeter (CC) tests showed that the peak heat release rate (pHRR) and peak smoke release rate (pSPR) during combustion of PPOPs/EP composites were reduced by 42.0% and 36.4%, respectively, compared with pure EP. Tensile tests showed that the addition of PPOPs improved the mechanical properties of the composites to some extent. In addition, PPOPs can be designed into different shapes for practical applications compared with those fragile inorganic insulation materials and powders that were usually non-processable. Taking these advantages into account, PPOPs have great potential for modern building applications as monolithic foams or coatings with both excellent flame retardancy and thermal insulation properties.